SARS-CoV-2 ORF3b Is a Potent Interferon Antagonist Whose Activity Is Increased by a Naturally Occurring Elongation Variant - Konno, Yoriyuki; Kimura, Izumi; Uriu, Keiya; Fukushi, Masaya; Irie, Takashi; Koyanagi, Yoshio; Sauter, Daniel; Gifford, Robert J.; Nakagawa, So; Sato, Kei (Cell reports (Cambridge), 2020)
One of the features distinguishing SARS-CoV-2 from its more pathogenic counterpart SARS-CoV is the presence of premature stop codons in its ORF3b gene. Here, we show that SARS-CoV-2 ORF3b is a potent interferon antagonist, suppressing the induction of type I interferon more efficiently than its SARS-CoV ortholog. Phylogenetic analyses and functional assays reveal that SARS-CoV-2-related viruses from bats and pangolins also encode truncated ORF3b gene products with strong anti-interferon activity. Furthermore, analyses of approximately 17,000 SARS-CoV-2 sequences identify a natural variant in which a longer ORF3b reading frame was reconstituted. This variant was isolated from two patients with severe disease and further increased the ability of ORF3b to suppress interferon induction. Thus, our findings not only help to explain the poor interferon response in COVID-19 patients but also describe the emergence of natural SARS-CoV-2 quasispecies with an extended ORF3b gene that may potentially affect COVID-19 pathogenesis. [Display omitted] •ORF3b proteins of SARS-CoV-2 and related animal viruses are IFN antagonists•SARS-CoV-2 ORF3b suppresses IFN more efficiently than its SARS-CoV ortholog•The anti-IFN activity of ORF3b depends on the length of its C terminus•An ORF3b with increased IFN antagonism was isolated from two severe COVID-19 cases COVID-19 pathogenesis is characterized by impaired IFN responses. Konno et al. identify ORF3b proteins of SARS-CoV-2 and related animal viruses as IFN antagonists. Their anti-IFN activity depends on the C-terminal length, and a natural ORF3b variant with increased IFN-suppressive activity was isolated from two severe COVID-19 cases.